Investigating the ferrimagnetic behaviour of trigonal 3C Fe7S8 nanoparticles - Jyotsna, Shubhra; Poddar, Pankaj (Bulletin of Materials Science, 2023)
The magnetic properties of trigonal 3C Fe7S8 nanoparticles, synthesized via the thermal decomposition method, are investigated using temperature-dependent zero-field cooled (ZFC) and field-cooled (FC) magnetization (M-T) curves. The M-T data, recorded at 100 and 1000 Oe, reveal magnetic ordering with high Curie transition temperature (T-C > 300 K) in the specimen. The magnetization vs. applied magnetic field (M-H) data measured in the temperature range from 7 to 300 K show that the compound exhibits ferrimagnetic ordering. The values of coercivity (H-C), saturation magnetization (M-60 kOe) and remanent magnetization (M-R) appear to increase at lower measuring temperatures. As the result of increasing M-60 kOe at lower measuring temperatures, within the temperature range of 7 to 300 K, the maximum energy product (BHmax) has the highest value of 128 kG Oe at 7 K.
Keywords: anisotropy; energy product; Fe7S8; ferrimagnetism; Pyrrhotites; trigonal phase